Occupational stress and its coping strategies among the police personnel of the Chitradurga city: a cross-sectional study - Furmeen, Sameeya; Reddy, Mayuri Reddy (International Journal Of Community Medicine And Public Health, 2019)
Background: Everyone relishes having a peaceful and safe society to live in. But nobody thinks about the police who work hard to keep our community safe and secure. They have to face potentially hazardous situations that can result in physical or mental trauma or even death in the line of duty. This study will help to reveal the stress and coping strategies employed by the police personnel of Chitradurga city. To determine the stressful situations faced by the police personnel and to ascertain the positive & negative coping strategies employed by the study participants. Methods: A cross sectional study was conducted among the police personnel in all the five police stations in Chitradurga city for a period of one year. Complete enumeration method was used to include 282 police men and women in the study. A pre-designed, pre-structured questionnaire was used to collect the data. The analysis was done using SPSS version 20. Appropriate statistical tests were applied. Results: The mean age of the participants was 36.13±10.33. Majority of them were males (89%), Hindus (95.4%), graduates (49.6%), living in their own house (38.7%), hailing from a nuclear family (62.1%) and belonged to socio-economic status class I (50%) according to modified BG Prasad’s classification. Conclusions: The stress was found to be significantly associated with work-related factors like difficulties in meeting deadlines, insufficient personal time, inadequate family time, needing changes in the department, eagerness to go to work and job satisfaction.